Social, cultural and historical determinants of childhood malnutrition in urban communities of Managua and San José - McGarrity, Gayle L. (Berkeley, Calif., 1993)
Tesis (doctorado de filosofía en antropología)--University of California at Berkeley, 1993.
Keywords: DESNUTRICION INFANTIL; DESNUTRICION -- ASPECTOS SOCIOECONOMICOS; POLITICA NUTRICIONAL -- COSTA RICA; POLITICA NUTRICIONAL -- NICARAGUA